Covid-19: Has the time come for mainstream macroeconomics to rehabilitate money printing? - Axelle Arquié; Jérôme Héricourt; Fabien Tripier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
The scale of public expenditure to be incurred in the Covid-19 health crisis is raising heated debates about the appropriate funding. Long rejected by mainstream macroeconomics due to its possible inflationary consequences, monetization is currently undergoing a surprising rehabilitation. Defined as the financing of public expenditure by money issuance - without the government ever reimbursing the central bank -, monetization appears as an attractive solution in a context where the burden of public debt could become particularly problematic due both to the persistent threat of secular stagnation and the massive Covid-19 shock. This policy brief offers some theoretical insights into this debate opposing monetization and issuance of additional public debt. We first clarify what is happening to current debt and how its sustainability can be assessed, before examining how current mainstream macroeconomics can be used to rehabilitate monetization of public spending. In conclusion, we draw attention to the particular democratic challenges implied by such a policy in the Euro area context, in terms of balance of powers between European institutions.
Keywords: E32; E52; E62; 330; Monetization; Covid-19; Seignorage; Government spending; Fiscal multipliers; Helicopter drop